Geriatric screening in first opinion practice: results from 45 dogs - Davies, M. (Wiley, 2012)
Objectives To evaluate and report the results of screening geriatric dogs in a first opinion practice. Methods A prospective health screen of dogs over nine-years-old involving history taking, physical examination and urinalysis. Results At least one previously unrecognised problem was identified in 80% of 45 dogs and 353 findings (mean 7·8 per dog) were recorded. Owners often failed to recognise and report serious signs of age-related disease. However, they most often reported increased sleeping (31%), loss of hearing (29%) or sight (20%), stiffness or lameness (22%) and “slowing down” (20%). Increased lens opacity (64%), increased thirst (58%), pain (24%), increased frequency of urination (24%), signs of osteoarthritis (24%) and dental disease (22%) were most frequently identified at the time of consultation. Potentially, life-threatening findings included respiratory distress, palpable abdominal masses and metastatic lung disease. Screening resulted in 29 further diagnostic procedures, including 10 dental procedures, seven medical treatments, two surgical procedures and euthanasia of two dogs. Clinical Significance Screening elderly dogs identified unrecognised and unreported health risk factors resulting in lifestyle modification and ongoing monitoring, as well as signs of age-related diseases resulting in diagnostic investigations, early diagnoses and surgical and medical interventions to improve quality of life.